Soft bimorph actuator with real-time multiplex motion perception. (October 2020) - Zhao, Hongtao; Hu, Run; Li, Pan; Gao, Anzhu; Sun, Xuantong; Zhang, Xiaohui; Qi, Xiangjun; Fan, Qiang; Liu, Yida; Liu, Xuqing; Tian, Mingwei; Tao, Guangming; et al.
Abstract: Soft actuators with accurate and real-time motion perception are of great importance for flexible machines and artificial intelligence robotics to enable an autonomic response to surroundings. To enhance the sensing-signal reliability and calibration, synchronous motion perception with multiplex feedback signals is desired but has not been sufficiently explored. Herein, we present a soft bimorph actuator that has electrical and visual dual channel signal feedback functions for real-time multiplex motion perception. Cellulose paper and polyimide tape were assembled together as bimorph actuation layers on which an MXene/graphene bilayer was coated for electrothermal function and electrical signal feedback and a thermochromic interlayer was used for real-time visual signal feedback. Based on the proposed actuators, three kinds of bionic robotics and an electro-puppetry robot, " Wu Song Fights the Tiger ", with motion-programmable features are demonstrated, revealing the broad application prospects of the present soft actuators in bionic soft robotics with real-time multiplexing motion perception. Graphical abstract: Here, we have developed a soft bimorph actuator which has thermochromic and self-sensing dual functionalities for real-time multiplex motion perception. Image 1 Highlights: A soft bimorph actuator that has thermochromic and self-sensing dual functionalities is proposed. The resulting bimorph actuators have been proven to have excellent actuating performances. The obtained actuator can realize real-time multiplex motion perception via colour shifting and output resistance. The actuator can be used in the fabrication of bionic robotics with motion-programmable features.